2020
DOI: 10.1111/opo.12770
|View full text |Cite
|
Sign up to set email alerts
|

Power profiles of centre–distance multifocal soft contact lenses

Abstract: Purpose Centre‐distance multifocal contact lenses (MFCLs) for myopia control are thought to slow myopia progression by providing both clear foveal vision and myopic defocus. Characterising the power profile of lenses is important to understanding their possible effects on retinal defocus when worn. The power profiles of three commercially available MFCLs were determined. Methods Three centre‐distance MFCL designs were studied: Biofinity Multifocal D +2.50 add (comfilcon A), Proclear Multifocal D +2.50 add (oma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…37 The NaturalVue lens is indicated to have effectively no central spherical optical zone, with relative plus power increasing almost immediately from the lens centre. 29,30 There are little data available for comparison with the accommodative instability results found here. One study found that a centre-distance MFCL had higher microfluctuations than an SV lens.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…37 The NaturalVue lens is indicated to have effectively no central spherical optical zone, with relative plus power increasing almost immediately from the lens centre. 29,30 There are little data available for comparison with the accommodative instability results found here. One study found that a centre-distance MFCL had higher microfluctuations than an SV lens.…”
Section: Discussionmentioning
confidence: 90%
“…Four commercially available MFCL lens types were used: MiSight concentric (+2.00 D add) (MS), Biofinity centre distance, continuous aspheric periphery with a +1.50 D (CD1) and a +2.50 D (CD2) add (all Coopervision, coopervision.com) and NaturalVue aspheric (Visioneering Technologies, vtivision.com) (NVue) which is reported by the manufacturers to be a ‘single high add’ and reaches a maximum relative plus power of +3 D to 5 D by 2.75 mm to 2.9 mm semi‐diameter ( Figure ) 29,30 . Each MFCL lens has a single base curve and single diameter, and all have been investigated for myopia control efficacy in children 8,31–34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The complete power profiles of the MiSight, Biofinity Multifocal D, and NaturalVue Multifocal have been previously published. 9,20 The MiSight lens has a centerdistance concentric ring design. The central 2-mm radius is for distance vision and is surrounded by rings of alternating near and distance zones.…”
mentioning
confidence: 99%
“…The lens was based on the NaturalVue contact lens (VTI, vtivision.com) which has an increase in sagittal power by approximately 4 D at a diameter of 6 mm. 20,21 It has a front surface with a central zone apical radius of curvature of 7.72 mm, matching that of the Navarro anterior cornea, but with conic asphericity Q = +0.753. A peripheral zone beyond a 6 mm diameter was continuous with the central zone, but was spherical with a 7.72 mm radius of curvature.…”
Section: Modelling and Raytrace Simulationsmentioning
confidence: 97%